An Overview on: Trade-Related Aspects of Intellectual Property Rights - Swatantra Kushwaha, Richa Sachan, Swati Maheshwari, Neelottama Kushwaha, A.K. Rai (Journal of Applied Pharmaceutical Science)
The World Trade Organisation’s (WTO) Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) substantially changed the international intellectual property regime by introducing the principle of minimum intellectual property standards. In effect, this principle means that any intellectual property agreement negotiated subsequent to TRIPS among and/or involving WTO members can only create higher standards – commonly known as “TRIPS plus”. The TRIPS-plus concept covers both those activities aimed at increasing the level of protection for right holders beyond that which is given in the TRIPS Agreement and those measures aimed at reducing the scope or effectiveness of limitations on rights and exceptions. Such intellectual property rules and practices have the effect of reducing the ability of developing countries to protect the public interest and may be adopted at the multilateral, plurilateral, regional and/or national level. The TRIPS Agreement addresses a wide range of intellectual property subject matter areas (copyright, trademark, patent, and so forth). It also covers competitive markets, enforcement measures, dispute settlement, and transitional arrangements. This Module provides an introduction to these various aspects of the TRIPS Agreement, and seeks to focus on the kinds of questions that should be asked when approaching dispute settlement. In some areas, the questions are answered, but the entire field of intellectual property rights protection, including enforcement measures, cannot be covered in a single module or short course. Moreover, the questions will change along with the technologies that form the subject matter of intellectual property rights protection. The objective of this Module is to provide sufficient background so that as specific issues arise, the diplomat or lawyer understands how to approach them.
Keywords: TRIPS, WTO, WIPO GATT, IPR.